Upaya pedagang kaki lima dalam mengatasi terpaan berita penyebaran Covid-19 di televisi - Intan Fadhilla; Ferdinandus Ngare (Islamic Communication Journal, 2020)
In a covid-19 pandemic situation like this, television media as information presenters, make social contributions by reporting to discussing social realities regarding the latest developments regarding the spread of the covid-19virus that is currently happening. In this case, news on television is the daily intake of the community, including the street vendors. Many media continued to launch and report the news to street vendors, who could not follow the government's directives to stay at home, because of the demands of work and the daily economy. However, the effect of news exposure is felt by street vendors and has its impact on them, so efforts are needed to overcome the exposure to the covid-19 news. This study aims to determine how the community's efforts to deal with exposure to covid-19 news on television. The research method used is a descriptive qualitative research method, using the theory of individual differences. The results of the research obtained from this research are street vendors in Cikedokan village, who are often exposed to news about covid-19 on television every day with a high frequency of broadcasts (often), so an effort to overcome exposure to the news is to limit yourself to watching. the latest news about covid-19 that is broadcast, besides that, street vendors are more selective in choosing good news for consumption so that it does not affect their attitudes and work in their day to day and do not forget to also obey government directions and ask more people. understand a situation like this pandemic.